2020
DOI: 10.1088/2053-1583/abc5a1
|View full text |Cite
|
Sign up to set email alerts
|

Strong exciton-photon coupling in large area MoSe2 and WSe2 heterostructures fabricated from two-dimensional materials grown by chemical vapor deposition

Abstract: Two-dimensional semiconducting transition metal dichalcogenides embedded in optical microcavities in the strong exciton-photon coupling regime may lead to promising applications in spin and valley addressable polaritonic logic gates and circuits. One significant obstacle for their realization is the inherent lack of scalability associated with the mechanical exfoliation commonly used for fabrication of two-dimensional materials and their heterostructures. Chemical vapor deposition offers an alternative scalabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Excitons in two-dimensional transition metal dichalcogenides (TMDs) have large oscillator strengths and binding energies [23], making them attractive as a platform for studies of strong light-matter coupling in optical microcavities [6][7][8][9]. A variety of polaritonic states have been realised using monolayers of MX 2 (M=Mo, W; X=S, Se) embedded in tunable [7,9,10,24] and monolithic microcavities [16,[25][26][27][28].…”
mentioning
confidence: 99%
“…Excitons in two-dimensional transition metal dichalcogenides (TMDs) have large oscillator strengths and binding energies [23], making them attractive as a platform for studies of strong light-matter coupling in optical microcavities [6][7][8][9]. A variety of polaritonic states have been realised using monolayers of MX 2 (M=Mo, W; X=S, Se) embedded in tunable [7,9,10,24] and monolithic microcavities [16,[25][26][27][28].…”
mentioning
confidence: 99%
“…Compared with the mechanical exfoliation technique, chemical vapor deposition (CVD) provides a scalable fabrication method for the deposition of 2D materials with wafer size, and thus is extremely attractive for the realization of in-plane devices. In 2020, Gillard et al observed strong exciton-photon coupling in a wide range of temperatures, based on microcavities composed of high-quality TMD monolayers encapsulated with large-area hBN [378] . These heterostructures are fabricated using CVD techniques and show high optical quality, comparable to mechanically exfoliated samples.…”
Section: Extended Monolayersmentioning
confidence: 99%
“…22 The other is the preparation of 2D materials by direct vapor-phase growth rather than by mechanical exfoliation. [23][24][25][26][27] In particular, recent advances in chemical vapor deposition (CVD) growth enable the preparation of large-area polycrystalline lms and single crystals of TMDC monolayers on a wafer-scale substrate. [28][29][30][31] In addition, triangular single crystals of TMDCs enable easy determination of the crystal orientation, allowing easy control of twist angles.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the use of such CVD-grown polycrystalline TMDC lms and single crystals has recently enabled fast, continuous fabrication of vdW heterostructures. [23][24][25][26][27] For example, Mannix et al demonstrated the fabrication of solid materials consisting of 80 layers of MoS 2 and twist-controlled 4-layer WS 2 , respectively, by using a robotic assembly with a multi-component polymer stamp. 26 Despite these great advances, there have been only a few reports on dry transfer and its effect on the optical properties of CVDgrown TMDCs.…”
Section: Introductionmentioning
confidence: 99%